¿Cuántas especies de zorros grises (Canidae, carnivora) hay en el sur de Sudamérica? - Chemisquy, Maria Amelia (2019)
Two species of grey foxes are recognized in the Southern Cone of America: Lycalopex griseus, and L. gymnocercus, which were traditionally separated by size and some cranial differences. Morphometric analyses of the skull showed that both species could be the same and that they show clinal variation, while DNA studies based on one mitochondrial marker suggested that they belong to different species. Our objective is to evaluate the systematic status of these foxes using three mitochondrial markers (cytochrome B, cytochrome oxidase I, and control region), and a large sample covering a wide geographic range. The results indicate that there are two clades, that are not sister taxa, a finding that is more congruent with the hypothesis of two species, but their geographic distribution is not coincident with the accepted distribution of L. griseus and L. gymnocercus. Consequently, the distribution of L. griseus is extended eastern including north and center of Argentina, towards the west and south of the Paraná, Paraguay and Río de la Plata rivers. On the other hand, the clade that probably represents L. gymnocercus is restricted to the east of those rivers, except for a few specimens collected in Santa Fe, close to the Paraná river. However, an analysis of a wider sample using nuclear DNA is needed to confirm the taxonomic identity of these species of grey foxes.